Amine-promoted asymmetric [4+2] cycloadditions of α-acetoxymethyl allenoate and dual activated alkenes: stereoselective synthesis of poly-substituted cyclohexenes. Issue 25 (17th June 2015) - Cheng, Mian; Liu, Jian-Kang; Tong, Xiaofeng; Tian, Ping
Graphical abstract: Abstract: A chiral secondary amine-promoted asymmetric [4+2] cycloadditions of α-acetoxymethyl allenoate1 and electron-deficient alkenes2 have been developed. The reaction features the utilization of addition–elimination reaction between allenoate1 and the secondary amine to generate the key 2-aminobutadiene intermediate, which subsequently undergoes [4+2] cycloaddition with alkenes in a stepwise fashion, delivering the substituted cyclohexenes with good stereoselectivity.